Fertility treatments and the risk of preterm birth among women with subfertility: a linked-data retrospective cohort study - Jessica N. Sanders; Sara E. Simonsen; Christina A. Porucznik; Ahmad O. Hammoud; Ken R. Smith; Joseph B. Stanford (BMC, 2022)
Plain Language Summary Infertility treatments such as in vitro fertilization are associated with preterm birth, but less is known about how other less invasive treatments contribute to preterm birth. This study compares different types of fertility treatments and rates of preterm birth with women who are also struggling with infertility but did not use fertility treatments at the time of their pregnancy. 490 women were recruited at the University of Utah between 2010 and 2012. Participants were asked to complete a survey and were linked to birth certificate and fetal death certificate data. Women who used in vitro fertilization were 4.24 times more likely to have a preterm birth than those who used no treatment. Use of intrauterine insemination were 3.17 times more likely to have a preterm birth than those who used no treatment at time of conception. Ovulation stimulating drugs were 2.17 times more likely to have a preterm birth. Having female factor infertility was also associated with higher odds of having preterm birth. For those who are having trouble conceiving, trying less invasive treatments to achieve pregnancy might reduce their risk of preterm birth.